Event Sastra Festival Temu Penyair Asia Tenggara II di Padang Panjang sebagai Potensi Pariwisata - Roma Kyo Kae Saniro; Andina Meutia Hawa; Donny Eros; Pramono Pramono (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2023)
This research aims to explore the literary event, theTemu Penyair Asia Tenggara II (TPAT) or Southeast Asian Poets Gathering II, as a potential tourism attraction. The background of this study lies in the existence of various literary festivals across the archipelago that have the potential to boost tourism, yet remain unknown to the wider public. One such event is held in Padang Panjang. This research investigates the impact of visitors' experiences on their return visits to the city where the festival takes place. The methodology employed in this research is a mixed-method approach, combining quantitative and qualitative methods. Quantitative methods were used to collect data through a survey questionnaire distributed to 14 respondents, covering 10 key indicators. Subsequently, the questionnaire data was processed using qualitative descriptive analysis with a focus on literary tourism. The research corpus is the TPAT II festival held in Padang Panjang, West Sumatra. Data collection involved distributing questionnaires to 14 correspondents, addressing 10 specific indicators. The research process included data collection through field surveys. The collected data was then processed and analyzed to reveal the literary event's potential as a tourism attraction, employing literary tourism perspectives. The findings of this research indicate that visitors perceive literature and tourism, as showcased in the festival held in Padang Panjang, positively. This perception leads to a desire among visitors to return to Padang Panjang. Visitor satisfaction is anticipated to serve as a model for organizing other festivals, acting as promotional platforms for lesser-known places or tourist destinations, thereby contributing to sustainable tourism. Consequently, regions hosting TPAT II events are expected to become tourism assets for Padang Panjang.